The Effect Of Variation of Pyrophyllite Addition To Compressive Strength, Porosity, And Diagram of Stress Strain In Burnt Lightweight Concrete Brick - Ristinah Ristinah; Retno Anggraini; Achfas Zacoeb; Prastumi Prastumi; Krisna Febrian Anugerahputra; I Dewa Nyoman Yoga Prawira (Rekayasa Sipil, 2013)
Lightweight brick is a material widely used in civil engineering as a substitute alternative material and brick walls of the building material. The aim of this study is to determine the behavior of burnt light brick, and behavior of piropilit additions in the mix proportion of the light brick. Specimens were tested by compressive strength, porosity, and modulus of elasticity. To test the compressive strength, plates were set at the top and bottom of the test specimen; a dial gauge was used to determine the deformation. To test the porosity, the specimen was cut into a size of 15 x 20 x 10 cm 3 and tested in accordance with porosity testing procedures. Data for the elastic modulus was obtained from stress and strain testing in conjunction with the compressive strength test. After the age of 28 days, specimens undergo combustion process before tested in the laboratory. Results of this study show that the addition of amount of piropilit as filler as much as 10-25% by weight of cement will increase the strength of brick light post-combustion at 800 o C temperature along with the increasing number of additional piropilit in it, however the addition of 5% would reduce the value of compressive strength. The addition of piropilit in the burnt lightweight brick will decrease the value of the strength. Porosity and modulus of elasticity values indicate that the addition of a filler piropilit as much as 515% by weight of cement on the burnt brick would increase the value of its porosity, however the addition of 20% and 25% would reduce the value of porosity. The modulus of elasticity values obtained from the stress and strain diagram, an increase of 5% -25% variation pyrophyllite additions. However there are some fluctuation trends on a variation of 5% -20% due to piropilit characteristics that do not fit to undergo the process of combustion or due to the setting position of the specimen in the furnace when the combustion process which allows the specimen exposed to direct flame or not.